PENGEMBANGAN MEDIA PEMBELAJARAN INFORMATIKA BERBASIS ANDROID MENGGUNAKAN SMART APPS CREATOR DI SMP NEGERI 4 CIAWIGEBANG - Rama Ananda Shepiar; Hifni Fitriah Nur Janah (STKIP Subang, 2026)
This study is motivated by an instructional approach that still relies on the lecture method and the use of textbooks, resulting in students appearing passive and struggling to comprehend the material. This study aims to develop an Android-based Informatics learning media using Smart Apps Creator for seventh-grade students at SMP Negeri 4 Ciawigebang, determine the feasibility level of the developed media, and identify user responses to the learning media. This study employed the Research and Development (R&D) method using the 4D development model, consisting of Define, Design, Develop, and Disseminate stages. The developed learning media contains Computer System materials equipped with text, images, instructional videos, interactive games, and quizzes. Data were collected through observation, interviews, and questionnaires. Product testing was conducted through alpha testing by media and material experts, followed by beta testing involving seventh-grade students. The results showed that the media expert validation obtained a percentage of 91%, categorized as “Highly Feasible”, while the material expert validation obtained 95%, categorized as “Highly Feasible”. In the beta testing stage, the small-group trial involving 10 students obtained a percentage of 92%, categorized as “Highly Feasible”, while the large-group trial involving 19 students obtained 91%, also categorized as “Highly Feasible”. Furthermore, the user response from 33 students obtained an average percentage of 87%, categorized as “Very Good”. Based on these results, the Android-based Informatics learning media developed using Smart Apps Creator was considered highly feasible and received very good user responses. Therefore, the media can be used as supporting learning media for Informatics subjects for seventh-grade students at SMP Negeri 4 Ciawigebang.